The molecular clock drives motivated locomotion and time-of-day-dependent firing patterns in mouse dopaminergic neurons - Ananya Swaroop; Jodi R. Paul; Laura J. McMeekin; Ashley M. Barnett; Alana M. Colafrancesco; Drèson L. Russell; Camille M. Smith; Micah S. Simmons; Laura A. Volpicelli-Daley; Rita M. Cowell; Karen L. Gamble (npj Biological Timing and Sleep)
Abstract Though circadian locomotor rhythms are primarily driven by the suprachiasmatic nucleus, voluntary motor behavior also requires dopaminergic neuron (DAN) activity. However, it is unknown whether DAN molecular and electrophysiological properties and rhythmic motor behaviors are dependent on a molecular clock. Here, we show substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) DANs rhythmically express clock genes, and conditional deletion of Bmal1 in DANs reduces motivated locomotion without robust cell loss or gross motor impairment. Further, DAN Bmal1 conditional deletion disrupts 24-h rhythms in spike rate, revealing ultradian rhythms (~4–8 h). Lastly, SNc DAN bursting varies across time of day and increased early night bursting is dependent on the molecular clock and L-type calcium channel activation. Collectively, we provide evidence of a cell-intrinsic dopaminergic clock which regulates key behaviors and physiology. Future studies should consider the contribution of disrupted DAN molecular clocks in age-related motor diseases like Parkinson’s Disease.